E-nose for basal stem rot detection - Ali Yeon, Md Shakaff, Prof. Dr.; Mazlee Noor, Ahmad. Dr.; Marni Azira, Markom; Abdul Hamid, Adom; Wahyu, Hidayat; Abu Hassan, Abdullah; N., Ahmad Fikri (Universiti Malaysia Perlis (UniMAP), 2010)
An electronic nose is an intelligent device, able to mimic human olfaction functions and may be used for detection, recognition and classification of volatile compounds and odours. An e-nose consists of an array of sensors, signal collecting unit(s) and suitable pattern recognition algorithm.